Holliday Junction Resolvase MOC1 Maintains Plastid and Mitochondrial Genome Integrity in Algae and Bryophytes. Issue 4 (25th September 2020) - Kobayashi, Yusuke; Odahara, Masaki; Sekine, Yasuhiko; Hamaji, Takashi; Fujiwara, Sumire; Nishimura, Yoshiki; Miyagishima, Shin-ya
Abstract : Monokaryotic Chloroplast1 acts in recombination surveillance of plastid and mitochondrial DNA in some algae and plants by preventing ectopic recombination between short dispersed repeats. Abstract: When DNA double-strand breaks occur, four-stranded DNA structures called Holliday junctions (HJs) form during homologous recombination. Because HJs connect homologous DNA by a covalent link, resolution of HJ is crucial to terminate homologous recombination and segregate the pair of DNA molecules faithfully. We recently identified Monokaryotic Chloroplast1 (MOC1) as a plastid DNA HJ resolvase in algae and plants. Although Cruciform cutting endonuclease1 (CCE1) was identified as a mitochondrial DNA HJ resolvase in yeasts, homologs or other mitochondrial HJ resolvases have not been identified in other eukaryotes. Here, we demonstrate that MOC1 depletion in the green alga Chlamydomonas reinhardtii and the moss Physcomitrella patens induced ectopic recombination between short dispersed repeats in ptDNA. In addition, MOC1 depletion disorganized thylakoid membranes in plastids. In some land plant lineages, such as the moss P. patens, a liverwort and a fern, MOC1 dually targeted to plastids and mitochondria. Moreover, mitochondrial targeting of MOC1 was also predicted in charophyte algae and some land plant species. Besides causing instability of plastid DNA, MOC1 depletion in P. patens induced short dispersed repeat-mediated ectopic recombination in mitochondrial DNA and disorganized cristae in mitochondria. Similar phenotypes in plastids and mitochondria were previously observed in mutants of plastid-targeted ( RECA2 ) and mitochondrion-targeted ( RECA1 ) recombinases, respectively. These results suggest that MOC1 functions in the double-strand break repair in which a recombinase generates HJs and MOC1 resolves HJs in mitochondria of some lineages of algae and plants as well as in plastids in algae and plants.